Analisis Minat Belajar Siswa Kelas IV SDN 13 Biru Kecamatan Tanete Riattang Kabupaten Bone di Era Pandemi Covid-19 - Andi Rizka Afdaliah Ashari; Sudarto Sudarto; Muliadi Muliadi (JPPSD:Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2021)
This research is a type of qualitative descriptive research that aims to determine the learning interest of fourth grade students at SDN 13 Biru, Tanete Riattang District, Bone Regency in the Covid-19 Pandemic Era. Data was collected by means of in-depth interviews. The analysis technique used is data reduction, data display, and conclusion drawing/verification. Students' learning interest can be seen from several descriptors, namely, when sending / depositing assignments, asking / not asking students, facial expressions, having personal cellphones or not, neatness of student books, neatness of student writing, and recording learning material. The results of this study indicate that the learning interest of fourth grade students at SDN 13 Biru, Tanete Riattang District, Bone Regency in the Covid-19 Pandemic Era is already fairly good because students always send or deposit assignments before the deadline, students always ask questions, students are always happy and excited, students have neat books and neat writing that is easy to read and students always take notes on the learning materials given by the teacher.